Achieving food security through live animal imports in the Gulf Cooperation Council countries. Issue 4 (2nd December 2020) - Gani, Azmat
Abstract : Purpose: This article examines the main factors that drive live animal imports in the Gulf Cooperation Council (GCC) countries in the Middle East. Design/methodology/approach: The analysis is based on a gravity model framework, and it incorporates annual data for imports of cattle, sheep and goats during the period 2004–2017 for six countries. The panel estimation technique is employed to disentangle the drivers of the GCC live animal imports. Findings: The results reveal that imports of live animals are consistently positive and statistically significantly correlated with the economic sizes of importer countries, liner shipping connectivity (LSC) (for cattle and goats) and culture (for cattle and sheep). Other determinants include falling tariffs for live cattle imports and falling costs of doing business for live sheep imports. Distance is found to exert statistically significant friction for imports of live goats. Practical implications: The GCC countries offer substantial opportunities for livestock trade to fulfil the growing demand for meat as a dietary requirement. Countries aiming at the GCC live animal segment of agricultural business would have to ensure reliable access to maritime transport connectivity and better understanding and insights into the business environment, transport logistics, trade policies, economic strength and cultural connections with meat consumption. The food-related supply chain system ought to have an extensive awareness of variables as the findings of this study revealed that can impact exchanges encountered across the supply chains. Originality/value: Until now, no study has empirically investigated the effect of live animal imports within a coherent trade theoretical framework in the GCC. The novelty of this research is that it makes the first attempt to identify the factors driving the extensive GCC live animal imports for meat consumption with a specific geographical focus. This study also complements the existing sparse empirical literature on trade-in live animals.